The Legality of Abortion Without Spousal Consent in Islamic Jurisprudence - Wahyudi Wahyudi; Usep Saepullah; Ibtisam Ilyana Ilias (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: The issue of abortion without spousal consent remains a contentious topic in Islamic jurisprudence, reflecting broader debates on women's autonomy and reproductive rights within marriage. Islamic family law traditionally emphasizes mutual agreement between spouses in major decisions, including those related to pregnancy. However, the question of whether a woman can independently decide to terminate a pregnancy without her husband’s approval remains subject to differing interpretations among scholars and legal schools. Purposes of the Research: This study aims to investigate the legality and ethical implications of unilateral abortion by women under Islamic jurisprudence, focusing particularly on the role and requirement of spousal consent. Methods of the Research: The research adopts a normative legal methodology, conducting a textual and thematic analysis of primary Islamic legal sources, including the Qur’an, prophetic traditions (Hadith), and the classical juristic rulings (fiqh), alongside contemporary scholarly opinions and legal frameworks in Muslim-majority countries. Results Main Findings of the Research: The findings reveal that while most Islamic legal traditions require spousal consultation or consent, certain conditions such as threats to the mother’s life or health may justify a woman's independent decision to abort. The study underscores a spectrum of legal opinions, from those mandating strict spousal consent to those permitting unilateral decisions based on the principle of avoiding harm (darar), and suggests that a balance can be achieved through a maqasid al-shari'ah (objectives of Islamic law) approach that prioritizes the well-being of the mother while respecting the marital partnership.